Screening of Natural Deep Eutectic Solvents for the Recovery of Valuable Phenolics From Waste of Shalgam Juice Process - Pelin Toprak; Ayşe Ezgi Ünlü (Turkish Journal of Agriculture: Food Science and Technology)
Shalgam juice is one of the most popular non-alcoholic beverages in Türkiye and also in many countries. The high amount of production, regarding the high amount of consumption leads to an inevitable amount of solid waste.  This amount reaches to almost 12 million kg of fermented black carrot annually. The accumulation of this waste causes fatal environmental pollution. The waste of shalgam juice process, fermented black carrot, retains significant amount of valuable components, such as phenolics, flavonoids, and anthocyanins. In this study new generation green solvents, Natural Deep Eutectic Solvents (NADESs) were screened for the extraction of valuable phenolics from fermented black carrot using ultrasound assisted extraction. The NADESs used were selected from four different groups such as acidic, sugar-based, choline chloride-sugar based and polyol-based. According to the results, the members of polyol and choline chloride sugar NADESs showed up. Choline chloride-glycerol (polyol group), extracted the highest total phenol amount (16.04 mg/g) and also provided the highest antioxidant activity (81.77%). On the other hand, NADESs belonging to choline chloride-sugar group were effective for the extraction of flavonoids and monomeric anthocyanins. Namely, choline chloride-fructose-water extract contained 21.45 mg/g of total flavonoids, while choline chloride-sucrose-water extract contained 1680.51 mg/kg of total monomeric anthocyanins. The performances of NADESs tested were found to be higher than that of water and ethanol showing the high yield recovery of valuable phenolics with NADESs. The results exhibited the significance of the components inside the waste. The remaining valuable content could be easily and efficiently extracted using NADESs and these extracts –as a mixture or after purification- can furtherly be used for different purposes in different fields, such as cosmetics, antioxidant preparations, etc, using a zero-cost waste as the input of the processes.